Cervical cancer risk and impact of Pap‐based screening in HIV‐positive women on antiretroviral therapy in Johannesburg, South Africa. Issue 3 (19th May 2017) - Rohner, Eliane; Sengayi, Mazvita; Goeieman, Bridgette; Michelow, Pamela; Firnhaber, Cynthia; Maskew, Mhairi; Bohlius, Julia
Abstract : Data on invasive cervical cancer (ICC) incidence in HIV‐positive women and the effect of cervical cancer screening in sub‐Saharan Africa are scarce. We estimated i ) ICC incidence rates in women (≥18 years) who initiated antiretroviral therapy (ART) at the Themba Lethu Clinic (TLC) in Johannesburg, South Africa, between 2004 and 2011 and ii ) the effect of a Pap‐based screening program. We included 10, 640 women; median age at ART initiation: 35 years [interquartile range (IQR) 30–42], median CD4 count at ART initiation: 113 cells/µL (IQR 46–184). During 27, 257 person‐years (pys), 138 women were diagnosed with ICC; overall incidence rate: 506/100, 000 pys [95% confidence interval (CI) 428–598]. The ICC incidence rate was highest (615/100, 000 pys) in women who initiated ART before cervical cancer screening became available in 04/2005 and was lowest (260/100, 000 pys) in women who initiated ART from 01/2009 onward when the cervical cancer screening program and access to treatment of cervical lesions was expanded [adjusted hazard ratio (aHR) 0.42, 95% CI 0.20–0.87]. Advanced HIV/AIDS stage (4 versus 1, aHR 1.95, 95% CI 1.17–3.24) and middle age at ART initiation (36–45 versus 18–25 years, aHR 2.51, 95% CI 1.07–5.88) were risk factors for ICC. The ICC incidence rate substantially decreased with the implementation of a Pap‐based screening program and improved access to treatment of cervical lesions. However, the risk of developing ICC after ART initiation remained high. To inform and improve ICC prevention and care for HIV‐positive women in sub‐Saharan Africa, implementation and monitoring of cervical cancer screening programs are essential. Abstract : What's new? Data on invasive cervical cancer (ICC) incidence in HIV‐positive women and the effect of cervical cancer screening in sub‐Saharan Africa are scarce. This South African cohort analysis found that ICC incidence substantially decreased after the implementation of a Pap‐based screening program and improved access to treatment of cervical lesions. However, ICC risk remained high in women who initiated ART at low CD4 cell counts. Patient‐level monitoring of screening programs is essential to improve ICC prevention.